THE PROTECTION OF RELIGIOUS FREEDOM OF SUNDA WIWITAN BELIEVERS - Hazar Kusmayanti; Dede Kania; Dede Mulyanto (Jurnal Hukum dan Peradilan, 2019)
Sunda Wiwitan as a religion had existed prior to the other, more well known religions in Indonesia, but is currently isn’t recognized as an official religion by Act No.1/PNPS/1965. The state, as opposed to guaranteeing the freedom of belief and its practice, instead imposes restrictions on religion in this particular case, leaving the believers of Sunda Wiwitan feeling abandoned and as outcasts. As a result, many violations and discriminations are experienced by adherents of Sunda Wiwitan. One example of such discrimination is the “whiting-out” of the “religion” column in ID Cards. The result of this discrimination is difficulty in accessing civil documents, in addition to verbal violence from certain parts of the society who assume the Sunda Wiwitan belief as heretic.